La[N(SiMe3)2]3‐Catalyzed Hydroboration of Esters and Other Challenging Unsaturated Groups1. Issue 11 (30th September 2019) - Xu, Xiaojuan; Kang, Zihan; Yan, Dandan; Xue, Mingqiang
Summary of main observation and conclusion: The commercially available homoleptic lanthanum amide La[N(SiMe3 )2 ]3 (LaN TMS ) is reported to enable the hydroboration of esters using pinacolborane (HBpin) as the reducing agent. A wide range of substrates including aromatic, aliphatic esters and lactones were applicable to afford corresponding boronic esters in excellent yields under mild and neat conditions with broad functional group compatibility and good chemoselectivity. Furthermore, LaN TMS is capable to realize the very challenging and rarely reported hydroboration of carbonate esters with low catalyst loading at room temperature. Both cyclic and linear carbonate esters can be easily converted to the corresponding products with satisfactory yields. Besides, the hydroboration of alkynes has been developed by using LaN TMS as a catalyst. Abstract :